2013
DOI: 10.1021/ic4013075
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Manganese and Cobalt Dichloride Monohydrate and Deuteration Effects on Magnetic Behavior

Abstract: This work reports the long sought crystal structures of the title members of the intriguing series of 3d transition metal dichloride monohydrates. The double chain structure which results from rearrangement of the well-known pseudo-octahedral coordination geometry and single chains in the corresponding metal chloride dihydrate is extremely unusual. MnCl2·H2O and CoCl2·H2O each crystallize in orthorhombic space group Pnma with Z = 4 and lattice parameters a = 9.0339(1), 8.8207(3); b = 3.68751(5), 3.5435(1); c =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This aqua ligand forms a hydrogen bond with a solvated water molecule providing a hydrogen bonding network that is expected if [Co­( 3 )­(OH 2 )­Cl] + is dissolved in an aqueous environment. An important structural feature among these complexes is a Co–Cl bond that is considerably longer (2.4–2.6 Å) than the Co–Cl bonds found in diimine or dioxime Co complexes (2.2–2.3 Å) and closer to the Co–Cl bond distance in CoCl 2 (2.44–2.51 Å). , The long Co–Cl bond lengths endow these bonds with more ionic than covalent character and may facilitate dissociation of a chloride ligand from the cobalt complex in a protic solvent such as water. All Co–N bond distances lie in a narrow range of 2.0–2.1 Å, regardless of whether the N-donor is part of a pyridine, phen, or quinoline moiety.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This aqua ligand forms a hydrogen bond with a solvated water molecule providing a hydrogen bonding network that is expected if [Co­( 3 )­(OH 2 )­Cl] + is dissolved in an aqueous environment. An important structural feature among these complexes is a Co–Cl bond that is considerably longer (2.4–2.6 Å) than the Co–Cl bonds found in diimine or dioxime Co complexes (2.2–2.3 Å) and closer to the Co–Cl bond distance in CoCl 2 (2.44–2.51 Å). , The long Co–Cl bond lengths endow these bonds with more ionic than covalent character and may facilitate dissociation of a chloride ligand from the cobalt complex in a protic solvent such as water. All Co–N bond distances lie in a narrow range of 2.0–2.1 Å, regardless of whether the N-donor is part of a pyridine, phen, or quinoline moiety.…”
Section: Resultsmentioning
confidence: 95%
“…The bromogroup was converted to acetyl through a Stille-type coupling with 1-ethoxyvinyl tri-n-butylstannane, followed by hydrolysis of the resulting vinyl ether. A second Friedlander condensation with 8-aminoquinoline-7-carbaldehyde provided the bridged ligands 38,39 The long Co−Cl bond lengths endow these bonds with more ionic than covalent character and may facilitate dissociation of a chloride ligand from the cobalt complex in a protic solvent such as water. All Co−N bond distances lie in a narrow range of 2.0−2.1 Å, regardless of whether the N-donor is part of a pyridine, phen, or quinoline moiety.…”
Section: ■ Resultsmentioning
confidence: 99%
“…These bond lengths are even longer than the Co−Cl bonds in cobalt dichloride that have been reported to range from 2.44 to 2.51 Å. 31,32 To the extent that the Co−Cl bonds have greater ionic character, they may account for better water solubility and more facile hydration, both important features for an effective homogeneous PRC. The N−Co−N bond angles of 6 are consistent with the metal ion being contained in either a fivemembered (83.1°and 81.7°) or a six-membered (92.9°) chelate ring.…”
mentioning
confidence: 99%
“…However, an additional hydrate with the composition MnCl 2 (H 2 O) is reported that shows an unusual structure, in which each Mn 2+ cation is octahedrally coordinated by one water molecule and five chloride anions. As it is the case for the dihydrate, the Mn 2+ cations are linked by μ‐1,1‐bridging chloride anions into chains, that are linked by μ‐1,1,1‐chloride anions to MnCl 2 double chains (Figure S3) [32] . If the water molecules are formally removed, these chains condense into the layered structure of MnCl 2 (Figure S3) [33] …”
Section: Resultsmentioning
confidence: 97%
“…As it is the case for the dihydrate, the Mn 2 + cations are linked by μ-1,1-bridging chloride anions into chains, that are linked by μ-1,1,1-chloride anions to MnCl 2 double chains (Figure S3). [32] If the water molecules are formally removed, these chains condense into the layered structure of MnCl 2 (Figure S3). [33]…”
Section: Comparison Of the Crystal Structures Of Mn(ncs) 2 (H 2 O) 2 ...mentioning
confidence: 99%